An Empirical Study on Determinants of Corporate Capital Structure:Evidence from UK - Dong, Handi (2011)
This paper examines the determinants of capital structure of FTSE 100 constituents UK listed companies over period from 2001 to 2010 using panel data. Several capital structure theories are reviewed in order to propose the testable hypotheses regarding the firms’ capital structure decisions in UK. To test these hypotheses, both pooled ordinary least square and fixed effects model are utilized. The result of the study shows that tangibility and firm size are positively relationship with all three gearing ratio which are short-term debt, long-term debt and total debt, while profitability and liquidity are inversely related to leverage. Growth opportunity is negatively relationship with short-term leverage, but positively relationship with long-term and total debt. Overall, the outcome of the research suggests that tangibility and liquidity are significant level of leverage, while profitability and firm size are significant level of long-term gearing ratio and total gearing ratio. Therefore, these independent variables have significant influence on capital structure.